Correlation Between BMI and HbA1c in Type 2 Diabetes Patients in Surabaya - Elfaretta, Zerlina Wina; Yuliawati, Tri Hartini; Susanto, Hermawan (Universitas 'Aisyiyah Yogyakarta, 2025)
Obesity is a well-established risk factor for Type 2 Diabetes Mellitus (DMT2), influencing disease severity and increasing the risk of complications. Regular HbA1c monitoring is a key component of effective diabetes management. Previous studies have indicated that individuals with higher Body Mass Index (BMI) tend to have elevated HbA1c levels, but this relationship has not been explored within the Surabaya population. This study aims to analyze the correlation between BMI and HbA1c levels in DMT2 patients at Dr. Soetomo Hospital in Surabaya. A cross-sectional, observational study was conducted to assess the correlation between BMI and HbA1c levels in DMT2 patients at the Endocrine Clinic of Dr. Soetomo Hospital. Data on weight, height, and HbA1c were collected and analyzed using the Spearman correlation test, with a p-value < 0.05 considered statistically significant. The study population consisted primarily of women aged over 40. Most patients were classified as obese (BMI ≥ 25 kg/m²), and the majority had uncontrolled HbA1c levels (>7%). A positive, linear correlation between BMI and HbA1c was found in the overall population (r = 0.228, p = 0.022) and in male patients (r = 0.29, p = 0.043). However, no significant correlation was observed in female patients (r = 0.125, p = 0.377). A significant positive correlation exists between BMI and HbA1c levels in DMT2 patients at Dr. Soetomo Hospital. Elevated BMI is associated with poorer glycemic control, particularly in male patients.